(untitled) (Nexus International Journal of Science and Education, 2024)
This study explored the influence of teachers’ instructional capability on the students’ eagerness to learn English in public elementary schools. In this study, the researcher selected the 220 public elementary school students in Babak District, Island Garden City of Samal as the respondents of the study. Stratified random sampling technique was utilized in the selection of the respondents. Non-experimental quantitative research design using descriptive-correlational method was employed. The data collected were subjected on the following statistical tools: Mean, Pearson Moment Product Correlation and multiple linear regression analysis. Findings revealed that teachers’ instructional capability and students’ eagerness to learn English in public elementary schools were described as extensive. Further, correlation analysis demonstrated that there is a significant relationship between teachers’ instructional capability and students’ eagerness to learn English in public elementary schools. Evidently, regression analysis proved that teachers’ instructional capability in terms of managing students’ conduct and encouraging intellectual creativity were significant predictors of students’ eagerness to learn English in public elementary schools in Babak District, Island Garden City of Samal. In other words, teachers’ instructional capability has influence on the process in students’ eagerness to learn English in public elementary schools. The study, therefore, conducted for further utilization of findings through publication in reputable research journal.